Obtenção de nanopartículas de ZnO dopado com nitrogênio para a reação fotocatalítica de redução do CO2 - Oliveira, Jéssica Ariane De (2016)
The environmental problems have been intensified by accumulation of carbon dioxide (CO2) in the atmosphere. Photocatalytic processes can be used to convert CO2 into other value-added compounds. For this purpose, semiconductors are used as photocatalysts and one of the most utilized is ZnO. The photocatalytic activity is usually improved by doping, thus, in this work, methods of synthesis of ZnO doped with N (ZnO:N) using urea as N source are analyzed. Four doping methods were evaluated by adding urea in the particles of: (1) amorphous ZnO and (2) crystalline ZnO; and in the solution of Zn (3) after polymerizing agent (PA) and (4) before PA. The materials were heat-treated (HT) in nine different conditions (400 °C, 450 °C and 500 °C for 2 h, 12 h and 24 h) and characterized by TGA/DTG, XRD, Raman, FTIR, XPS, DRS, BET and SEM-FEG. By TGA/DTG it was noticed that the temperature of 400 oC was not appropriate for synthesis of the particles. By XRD, it was observed that the samples are in the wurtzite phase of ZnO, the crystallites are in nanometer scale and they increase their size with the increment in the temperature and time of HT. By Raman and FTIR, it was verified that higher times of HT and/or the methodology 4 (M4) provide samples with higher symmetry and less contaminants adsorbed in the surface. By XPS, it was identified the doping of N in the crystalline structure of some previously select samples. By DRS, it was found that pure ZnO has lower band gap than the reported in the literature, fact that is related to the synthesis method. Then, it was identified that particles synthesized in higher times of HT and/or by the M4 have greater definition of crystallinity and lower quantity of residues of synthesis. Other characterizations were done for pure ZnO (ZP) and the samples of ZnO:N synthesized by M4. By BET and SEM-FEG, it was observed a tendency in the decrease of surface area with the increase in the temperature of HT due to the formation of clusters in higher temperatures of HT. Therefore, it was used ZP and the samples synthesized by M4 as photocatalysts in the reaction of photoreduction of CO2. The progress in the reaction was monitored by CH4 production. It was noticed that lower times of HT provide materials with better photocatalytic activity since the higher quantities of CH4 were identified for the samples synthesized by M4 e submitted to heat treatment at 450 ºC for 2 h and 500 ºC for 2 h.